Quantifying the Impact of Patient-Specific Factors and Disease Severity on Clinical Decision Making in Cuff Tear Arthropathy: A Case-Based Survey. Issue 3 (October 2019) - Schumaier, Adam P.; Bedeir, Yehia H.; Dines, Joshua S.; Kenter, Keith; Gulotta, Lawrence V.; Dines, David M.; Grawe, Brian M.
Background: Rotator cuff tears are a common cause of disability. Some patients with massive and irreparable tears can develop cuff tear arthropathy (CTA), which makes management more challenging. Questions/Purposes: We sought to examine how orthopedists determine treatment for patients with CTA. Specifically, we investigated (1) the effect of patient age, symptoms, activity level, range of motion, and radiographic findings on the decision making of shoulder specialists and (2) the observer reliability of the Seebauer and Hamada grading systems. Methods: Five shoulder surgeons were each sent 108 simulated patient cases. Each simulated patient had a different combination of factors, including patient age, symptoms, activity level, range of motion, and radiographs. Responders graded the radiographs and chose a treatment (non-operative, arthroscopic, hemiarthroplasty, or reverse total shoulder arthroplasty). Spearman's correlations and χ 2 tests were used to assess the relationship between factors and treatments. Sub-analysis was performed on surgical cases. An intra-class correlation (ICC) was used to assess observer agreement. Results: The significant Spearman's correlations were symptoms (0.45), Hamada grade (0.38), patient age (0.34), and Seebauer type (0.29). In sub-analysis of operative cases, the significant correlations were Hamada grade (0.56), patient age (0.51), Seebauer type (0.46), activity level (−0.13). The χ 2 analysis was significant for all factors except activity level. The inter- and intraobserver reliabilities were, respectively, Seebauer type (0.59 and 0.63) and Hamada grade (0.58 and 0.65). Interobserver reliability for patient management was 0.44. Conclusion: When evaluating CTA, patient symptoms, radiographic grade, and patient age are the factors most strongly associated with the decision making of shoulder specialists. Additionally, the Seebauer and Hamada classifications had similar reliability and clinical utility. However, there was only fair agreement regarding treatment, which indicates that CTA management remains controversial.